An Overview on Japan and Malaysia Peat Relating to Geotechnical Characteristic - Abu Talib, Mohd Khaidir; Yasufuku, Noriyuki (International Journal of Integrated Engineering, 2014)
Peat deposits distribution is extensive and can be found in many countries throughout the world when the conditions are favorable for their accumulation and formation at different climatic zones. These deposits represent the extreme form of soft soil and subject to instability and enormous primary as well as long-term settlement even when subjected to moderate load. Access to these superficial deposits is usually very difficult as the water table will be at near or above the ground surface. To sum up, peat is considered as unsuitable soils for supporting foundations or any construction works in its natural state. This paper presents some review of peat soil from Japan and Malaysia pertaining to geotechnical properties in order to develop and expand an understanding about tropical peats for future studies. The parameters studied were the moisture content, loss on ignition, unit weight, specific gravity (Gs), fiber contents, acidity, liquid limit (LL), plastic limit (PL), plastic index (PI) and shear strength. Overall, Hokkaido peat that had been studied has many similarities of peat properties with Malaysia peat especially in West region including Johor peat.